Cell-Free Protein Synthesis - Biyani, Manish (IntechOpen, 2012)
The Nobel Prize in Medicine 1968 for interpretation of the genetic code and its function in protein synthesis and in Chemistry 2009 for studies of the structure and function of the ribosome highlighted the ground-breaking experiment performed on May 15, 1961 by Nirenberg and Matthaei and their principal breakthrough on the creation of "cell-free protein synthesis (CFPS) system". Since then the continuous technical advances have revitalized CFPS system as a simple and powerful technology platform for industrial and high-throughput protein production. CFPS yields exceed grams protein per liter reaction volume and offer several advantages including the ability to easily manipulate the reaction components and conditions to favor protein synthesis, decreased sensitivity to product toxicity, batch reactions last for multiple hours, costs have been reduced orders of magnitude, and suitability for miniaturization and high-throughput applications. With these advantages, there is continuous increasing interest in CFPS system among biotechnologists, molecular biologists and medical or pharmacologists.